End-product of fibrinogen is elevated in emphysematous chronic obstructive pulmonary disease and is predictive of mortality in the ECLIPSE cohort. (November 2019) - Manon-Jensen, Tina; Langholm, Lasse L.; Rønnow, Sarah Rank; Karsdal, Morten Asser; Tal-Singer, Ruth; Vestbo, Jørgen; Leeming, Diana Julie; Miller, Bruce E.; Bülow Sand, Jannie Marie
Abstract: Background: Chronic obstructive pulmonary disease (COPD) is characterized by abnormal epithelial repair process that may result in intra-airway accumulation of fibrin. Given that plasma fibrinogen is the only FDA approved biomarker that predicts mortality and COPD exacerbations, we hypothesized that changes in the processing of fibrinogen may provide additional characterization of disease phenotype and COPD progression. Methods: A subpopulation of subjects with COPD, (n = 983) smoker (n = 205) and non-smoker controls (n = 98) were included from The Evaluation of COPD Longitudinally to Identify Predictive Surrogate End-points (ECLIPSE) cohort. Two biomarkers that specifically target the thrombin-mediated conversion of fibrinogen into fibrin (PRO-FIB), and plasmin-mediated degradation of cross-linked fibrin (X–FIB) were measured and compared with fibrinogen measurements. Results: X–FIB had a predictive value for two-year mortality, with an adjusted hazard ratio of 1.48 per SD (n = 980; 95% Cl 1.18–1.84; p < 0.0001), and comparable to the fibrinogen hazard ratio of 1.59 per SD (n = 983; 95% Cl 1.29–1.96; p = 0.0003). X–FIB (p < 0.001), fibrinogen (p < 0.0001) and PRO-FIB (p < 0.05) were significantly elevated in symptomatic COPD (mMRC ≥ 2) as compared to asymptomatic COPD. X–FIB was the only biomarker that was associated with emphysema (p < 0.001), and only plasma fibrinogen (p < 0.05) was associated with exacerbations. Conclusion: There is a need for biomarkers to characterize the heterogeneity of COPD, to continuously improve clinical trial design and to identify disease progressors for efficient health care utilization. Each of three fibrinogen biomarkers studied provide information representing distinct aspects of COPD which may be used to characterize disease endotypes and to assess mortality risk in COPD. Highlights: There is an immediate need for accurate and precise biochemical markers to characterize the heterogeneity of COPD. Plasma fibrinogen is the only FDA approved biomarker that predicts mortality and COPD exacerbations. Changes in the processing of fibrinogen may provide additional characterization of disease phenotype and COPD progression. Each of the three fibrinogen biomarkers studied provide information representing distinct aspect of COPD. X-FIB may serve as a biomarker for predicting disease phenotype by identifying patients with emphysematous COPD.